A protocol for size separation of nanographenes. Issue 58 (21st October 2019) - Matsumoto, Ikuya; Sekiya, Ryo; Haino, Takeharu
Abstract : Top-down methods are convenient preparative methods for nanographenes, although the products consist of graphene fragments with a broad size distribution. We developed a simple protocol for size separation of nanographenes. Abstract : Top-down methods are convenient preparative methods for nanographenes, although the products consist of graphene fragments with a broad size distribution. We show that a combination of dialysis membranes (50, 25, 15, 8, and 2 kD) can conveniently separate nanographenes into five size distributions. The separated nanographenes can be employed as starting materials for carbon-based functional materials.